Determinan of Fraud Prevention in Public Procurement of Goods and Services: A Systematic Literature Review - Lasri ningsih; Haliah Haliah; Nirwana Nirwana (International Journal Of Economics Social And Technology, 2023)
The number of cases of fraud in the procurement of public goods and services that have occurred in Indonesia shows that government transparency and accountability are still inadequate and so a prevention effort is needed to overcome the many cases of fraud in the procurement of goods and services that occur. The purpose of this study is to determine the key factors that can prevent fraud in the procurement of public goods and services in the Indonesian government. The research method used in this study is the systematic literature review (SLR) method based on 15 articles published from 2016-2023 in the Google Scholar journal database that meet the requirements for analysis. The results of this study found that the most influential factors (determinants) in preventing fraud in the procurement of public goods and services are Internal Control, E-Procurement, Organizational Culture and Whistlebowling System.